Phytochemical screening and GC-MS analysis of Skimmia laureola Decne. leaves from the Kumaon Region of Uttarakhand, India - Jyoti Darmwal; Pushpa Joshi Vandana Koshyari
Skimmia laureola (DC.) Decne. is one of the most important traditional medicinal plants in the Rutaceae family, found in the Western and Eastern Himalayan regions. Whole plants are well-known for their ethnobotanical and medical uses. Looking at its traditional medicinal uses, the present study aimed to determine the phytochemicals through preliminary phytochemical screening and to profile the bioactive compounds in the different solvent extracts of S. laureola using the GC-MS technique. The phytochemical analysis revealed the presence of alkaloids, carbohydrates, flavonoids, coumarins, steroids and terpenoids in all three extracts. The GC-MS analysis identified various phytoconstituents with varying concentrations and molecular masses in each extract. Methanol extract revealed 57 compounds, ethyl acetate extract showed 73 compounds and 53 compounds were obtained from n-hexane extract. The predominant compounds were dictamnine (19.72%), methoxsalen (11.56%) in methanol extract, dictamnine (16.37%), cycloeucalenol acetate (15.27%) in ethyl acetate extract and tetracontane (19.35%), cycloeucalenol acetate (16.16%) in n-hexane extract. Some constituents such as Cycloeucalenol acetate and 13,27-Cycloursan-3-one identified as triterpenoid compounds were observed and had not been previously reported. This suggests the potential of this plant as a cost-effective source of dictamnine and methoxsalen, which are already known for their therapeutic properties. Further detailed investigations are needed to elucidate the therapeutic effects of these phytochemical constituents.